Evaluasi pengeringan kunyit menggunakan pengering rak vertikal sumber energi sekam padi metode konveksi paksa - Ida Bagus Alit; I Gede Bawa Susana (AGROINTEK, 2022)
The drying process carried out in the open is prone to exposure to dust and animal waste. In addition, it takes a long time and is very dependent on the weather. The purpose of this research is to thermally evaluate a forced convection type vertical shelf dryer using rice husk energy using a single furnace model. This is done through the conversion of rice husks into thermal using a heat exchanger. Rice husks are burned directly in a furnace equipped with heat exchange pipes. This pipe functions to circulate heated environmental air into the drying chamber with the help of an exhaust fan. The test was carried out to dry a sample of white turmeric with a mass of 3191 grams for 600 minutes. The sample mass is evenly distributed on 4 vertical shelves in the drying chamber. The test results show that the ambient temperature increased by an average of 73.57%, namely from 28.57oC to 49.58oC. This temperature is the average temperature that occurs in the drying chamber in the turmeric drying process. The average drying temperature on each shelf differs depending on the distance from the heat source. On shelves 1, 2, 3, and 4, respectively, they are 54.21oC, 50.93oC, 47.62oC, and 45.57oC. Overall, the water content of white turmeric after drying reached 6.335% from the initial water content of 79.6%. The average efficiency of the dryer is 32.97%. During the drying process, there is a decrease in efficiency. This is because the energy absorbed by white turmeric decreases due to reduced water content.    This dryer model can be used as an alternative in post-harvest handling for small farmers that is energy efficient and sustainable.